PHYSICS OF REMOTE GAMMA THERAPY - Elmurotova Dilnoza baxtiyorovna; Kattaxodjayeva Dinara Utkurxodjayevna; Jaxongirova Shaxrizoda Ulug’bek qizi; Yusupova Madina Baxromovna (Web of Journals Publishing, 2025)
The work presents the physical concept of gamma radiation. The main processes that occur when gamma radiation passes through matter. It shows the advantage of gamma therapy and ways to obtain gamma radiation, as well as the half-life of the isotope, which is the source of gamma radiation.